GS. Trần Hồng Quân - Bộ trưởng Bộ Giáo dục và đào tạo giải trình một số vấn đề tại kỳ họp thứ 9 Quốc hội khóa IX - Bộ Giáo dục và đào tạo; Bộ Giáo dục và đào tạo (Văn phòng Quốc hội, 1996)
Electronic Resources